The murta (Ugni molinae) and its beneficial health properties: A review (Scientia Agropecuaria, 2021)
Currently there is a great demand for food products containing functional properties and/or bioactive compounds. One of the fruits that has been widely studied is the murta (Ugni molinae), which appears to contain various beneficial health properties. This review compiles scientific information on the functional and beneficial properties of murta for human health, such as the main components associated with anti-inflammatory activity, antimicrobial activity, antioxidant activity, nutritional composition, other uses of murta, economic aspects, and current and future challenges of murta, all based on updated scientific work.
Keywords: murta; flavonoids; antioxidants; antibacterial; anti-inflammatory; functional food